PENGARUH KOMITMEN ORGANISASI DAN PENGETAHUAN MANAJER TERHADAP KEBERHASILAN PENERAPAN SISTEM INFORMASI AKUNTANSI - Witaliza, Wulan; Agusti, Restu (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
The objective of this study is to examine the impact of organizational commitmentand knowledge manager on success of implementation accounting informationsystem. The study was conducted survey method; consist of 63 managers in PT.Angkasa Pura II (Persero). The study tested hypothesis using multiple regressionanalysis model.The result of this study show that the organizational commitment andknowledge manager, significance effect on success of implementation accountinginformation system.Keyword: organizational commitment, knowledge manager, success ofimplementation accounting information system.